Solar suitability tool and maps developed by WLE/IWMI now used by private sector actors to expand solar pump supply chains across sub-Saharan Africa - CGIAR Research Program on Water, Land and Ecosystems (2020)
A set of online interactive maps have been developed by WLE/IWMI to show the highest-potential locations for targeting small solar-powered irrigation pumps to smallholder farmers. Millions of farmers can substantially increase their incomes using these pumps. The tool is used to inform planning and management of sustainable solar pump irrigation dissemination in sub-Sahara Africa. Several project partners, i.e. solar manufacturing and distribution companies, are using the maps to expand their distribution and supply chains.